2020
DOI: 10.1111/jcmm.15929
|View full text |Cite|
|
Sign up to set email alerts
|

Remifentanil up‐regulates HIF1α expression to ameliorate hepatic ischaemia/reperfusion injury via the ZEB1/LIF axis

Abstract: Ischaemia/reperfusion (I/R)‐induced hepatic injury is regarded as a main reason of hepatic failure after transplantation or lobectomy. The current study aimed to investigate how the opioid analgesic remifentanil treatment affects I/R‐induced hepatic injury and explore the possible mechanisms related to HIF1α. Initially, an I/R‐induced hepatic injury animal model was established in C57BL/6 mice, and an in vitro hypoxia‐reoxygenation model was constructed in NCTC‐1469 cells, followed by remifentanil treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
2
1
0
Order By: Relevance
“…Specifically, the restraint of Bax by AKT suppresses apoptosis by reducing caspase 3 activity 45,46 . A recent study found that activated phosphorylated AKT dramatically mitigates IRI in the liver 47 . In the present study, we found that the PI3K/AKT/mTOR pathway was significantly suppressed after hepatic IRI but could be activated by HDAC6 deletion.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, the restraint of Bax by AKT suppresses apoptosis by reducing caspase 3 activity 45,46 . A recent study found that activated phosphorylated AKT dramatically mitigates IRI in the liver 47 . In the present study, we found that the PI3K/AKT/mTOR pathway was significantly suppressed after hepatic IRI but could be activated by HDAC6 deletion.…”
Section: Discussionsupporting
confidence: 58%
“…45,46 A recent study found that activated phosphorylated AKT dramatically mitigates IRI in the liver. 47 In the present study, we found that the PI3K/ AKT/mTOR pathway was significantly suppressed after hepatic IRI but could be activated by HDAC6 deletion. Moreover, HDAC6 overexpression produced the opposite trend.…”
Section: Discussionsupporting
confidence: 51%
“…In Rongsheng Zhou et al, 1 incorrect images were used in Figure 1B , Figure 2D , Figure 3M and Figure 5I . The correct figures are shown below.…”
mentioning
confidence: 99%